A study of Diglossia: a survey of different English varieties used by UTAR English Language course student - Low, Joey Xiao Xuan (2011)
This research project reports a study of diglossia by conducting a survey of English varieties used by the university students in Malaysia. In particular, the study seeks to examine the university students’ language choice and reasons, as well as their language attitudes. Questionnaire technique was used to elicit data from university students in Universiti Tunku Abdul Rahman who are pursuing their degree course in English Language. It follows from the findings on language choice that the relationship between Standard English and Malaysian English is diglossic. As for the language attitudes, perhaps due to the course major, most respondents have a positive attitude towards Standard English rather than towards Malaysian English in all aspects. However, most respondents think that the Malaysian English is replacing Standard English to become the more widely spoken variety among Malaysians. Thus, the diglossic relationship between Standard English and Malaysian English is likely to continue in Malaysia. Findings of the study shed light on the diglossic situation of English language in a multilingual country as well as reflect the opinions of the youth in Malaysia on the two distinct English varieties that have existed in their community.